Enteral nutrition support and nursing care for a patient with superior mesenteric artery syndrome secondary to Ewing's sarcoma (1例尤文肉瘤继发肠系膜上动脉压迫综合征患者的肠内营养支持和护理) - TIAN Li (田丽); ZHENG Xi (郑溪); CAI Jingjing (蔡晶晶); LIANG Bin (梁斌); HOU Seng (侯森); ZHONG Changkun (仲长鲲) (中西医结合护理)
This paper retrospectively analyzed clinical data pertaining to a patient who experienced weight loss due to chemotherapy-induced Ewing's sarcoma, subsequently leading to the development of superior mesenteric artery syndrome (SMAS). Based on the comprehensive evaluation of patient condition, the patient underwent intestinal nutritional support using a three-lumen gastrojejunal tube. In addition to standard nutritional support and care, healthcare professionals conducted targeted pre-nutritional screening and assessment, considering the patient's age and growth characteristics. Collaborating closely with the medical team, specific care protocols for enteral feeding via the three-lumen gastrojejunal tube were meticulously devised to facilitate seamless implementation of intestinal nutritional support in a home environment. The multidisciplinary team-based interventions not only ensure the safety and effectiveness of enteral nutritional support in the hospital, but also lay a solid foundation for the smooth transition to home-based enteral nutritional support, realizing the continuity and completeness of treatment and nursing. (本研究总结1例尤文肉瘤化疗导致体质量下降继发肠系膜上动脉压迫综合征(SMAS)患者的营养支持和护理实践经验。基于患者综合情况, 选用三腔喂养管肠内实施营养支持治疗。除常规营养支持护理外, 护理团队根据患者年龄特征及生长发育需求, 实施个体化营养风险筛查与评估, 协同医疗团队优化治疗方案, 并制定系统化的三腔喂养管肠内营养支持护理方案。通过多学科协作的精细化护理管理, 不仅确保了院内肠内营养支持的安全性和有效性, 同时为顺利过渡至家庭肠内营养支持奠定了坚实基础, 实现了治疗及护理的连续性和完整性。)